Analysis using Non-Functional Static Testing Framework - Priyanka R, Bhuyar; Gawande, AD (International Journal of Computer Sciences and Engineering, 2015)
Static Testing Techniques are widely used throughout SDLC and proved very effective increasing effectiveness of testing by uncovering and preventing defects at early stage. Static Testing techniques for functional aspects of software are well defined and matured compared to static testing techniques for Non functional aspects of software. In this project, we designed Non Functional Static Testing Framework with details such as processes, roles, test scenarios, implementation guidelines. Framework helps to use correct NF static technique at correct place (which technique to use, where to use it in SDLC, how to use). We strongly believe that NF static testing framework is a novel idea and fulfill several goals in increasingly complex non-functional domain, thereby reducing business risks at optimal cost and schedule.